GLOBALIZAREA ȘI IMPACTUL EI ASUPRA MEDIULUI DE SECURITATE INTERNAŢIONAL - Furtună, Petru; Efremov, Valeriu (My University, 2019)
Procesul de desfășurare a globalizării este un process deosebit de dinamic de creștere a interdependențelor între state cu efecte economice, politice, sociale, militare și ecologice, care implică diverse beneficii, dar și noi riscuri, pericole și amenințările la adresa securității internaționale. Articolul discută aspectele teoretice ale globalizării și impactul acesteia asupra mediului internațional de securitate.

International security and stability is threatened by international terrorism - the most painful plague of the contemporary world. Given the importance of this issue, it is of course the increased interest of researchers in studying and analyzing this phenomenon. This article attempts to review and analyze the theoretical aspects discussed in the literature, especially the concept and definition of international terrorism, as well as its classifications. The different scholars’ approaches to the concept of international terrorism, its classification on the basis of different criteria and the importance of these efforts of the political and academic community are outlined.
Keywords: globalizare; securitate; relații internaționale; stat național; terrorism; security